ID 304 – A comparison of the cerebral networks activated by painful and non-painful stimulations in humans: an intra-cerebral recording study. Issue 3 (March 2016) - Perchet, C.; Frot, M.; Vartiainen, N.; Claude, L.; Garcia-Larrea, L.; Bastuji, H.
Abstract : We highlight and compare the different cerebral networks responding to the activation of the spinothalamic (STT) and lemniscal (LT) pathways. Eight epileptic patients (6 men, 34 ± 10 years) with intracortical implanted electrodes participated to the experiment. A non painful tactile (LT) and two painful stimuli, laser Nd:YAP (STT) and concentric electrode (STT+LT), were delivered on the dorsum of the hand contralateral to the electrode implantation. Evoked responses to the three types of stimulation were analysed in term of latency, amplitude and topography, in various cortical areas. Responses of similar morphology were recorded in posterior insula, supra-sylvian operculum and parietal cortex (BA 40), their latencies being longer for laser as compared to the others. In the mid cingulate gyrus and the premotor cortex (BA 6), while responses to laser and concentric stimuli were present, those of tactile ones were inconstant. In the anterior insula, only the responses to laser stimuli were observed. These preliminary results suggest that the cortical networks have different patterns of temporal and spatial activation according to the somatosensory pathway stimulated.